2014
DOI: 10.1186/1471-2407-14-241
|View full text |Cite
|
Sign up to set email alerts
|

p21 and CD166 as predictive markers of poor response and outcome after fluorouracil-based chemoradiotherapy for the patients with rectal cancer

Abstract: BackgroundPre-operative chemoradiotherapy (CRT) is the standard treatment in clinical stage T3/4 or node positive rectal cancer. However, there are no established biomarkers that can predict the pathological response and clinical outcome to CRT.MethodsImmunohistochemical staining was performed in tissue arrays constructed from core tissue specimens taken before treatment and from operative specimens from 112 patients who received 5-FU based pre-operative CRT and surgery. Expression of Ki67, TS, BAX, EpCAM, p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 29 publications
(39 reference statements)
4
37
0
2
Order By: Relevance
“…The critical mechanism by which p21 cip1 suppresses CS-like properties is controversial [3639]. Here, we demonstrated a critical mechanism for the inhibition of Wnt/β-catenin pathway activity by p21 cip1 in CRC.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The critical mechanism by which p21 cip1 suppresses CS-like properties is controversial [3639]. Here, we demonstrated a critical mechanism for the inhibition of Wnt/β-catenin pathway activity by p21 cip1 in CRC.…”
Section: Discussionmentioning
confidence: 60%
“…However, the role of p21 cip1 in reducing the CS-like cell population is controversial. Studies have suggested that p21 cip1 expression promoted tumor regression and poor prognosis in 112 cancer patients [36, 37], but other studies reported that p21 cip1 expression reduces stem cell properties [38, 39]. Notably, increased p21 signaling in CRC inactivates the Wnt/β-catenin pathway [40].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-17 directly inhibits the p21 expression in myeloid leukemia [25] and promotes the tumor growth by suppressing p21 in synovial sarcomas [26]. In addition, some previous studies showed that the deletion of p21 led to poor survival prognosis in some cancers [27][28][29][30]. However, the role of the loss of p21 has not been conclusively determined in the clinical outcome of NPC.…”
Section: Introductionmentioning
confidence: 99%
“…8 Genetic factors may influence the response to chemoradiotherapy and the pCR rate, although there is some debate as to the benefit of some biomarkers. [14][15][16][17] the prognostic differences between t3 early invasion (≤5 mm) compared with more advanced invasion (>5 mm) have been demonstrated. 18 local recurrence rates and 5-year survival rates were improved in t3 patients with early invasion.…”
mentioning
confidence: 96%